Domestic Institutions and Global Value Chains: Offshoring in Germany's Core Industrial Sectors. (27th November 2018) - De Ville, Ferdi
Abstract: Do domestic institutions affect industrialised countries' positions in global value chains? A key insight from literature on global value chains is that a firm's decision to offshore depends on the trade‐off between price competitive gains and coordination costs. The role of domestic institutions in this decision has largely been neglected in global value chains analyses. However, a core insight from literature on varieties of capitalism is that the outcome of this trade‐off differs depending on the national institutions in which firms are embedded. National economies vary in terms of the importance of non‐market institutions for firms' production decisions. This article integrates insights from both literatures, resulting in the hypotheses that for firms in coordinated market economies offshoring has lower gains and higher costs than for firms in liberal market economies and that this will translate in a different importance and/or geography of global value chains. We empirically test these hypotheses by focusing on Germany. We find that Germany is intensively integrated in international value chains, but that its core sectors have made relatively more use of 'near shoring', as this allows them to retain comparative institutional advantages. This has permitted Germany to maintain and even expand output and employment in industry. Abstract : In a political climate where globalisation and offshoring are often seen as indiscriminately having resulted in a loss of manufacturing jobs in developed economies, we have shown that this does not apply to Germany.